The influence of human factors on operational efficiency - Harris, Don (Emerald, 2006)
This paper adopts a socio-technical systems approach is taken to examine how airline operational efficiency can be enhanced from a human factors perspective. Four case studies are examined from this viewpoint: increasing operating efficiency on the airport ramp; increasing efficiency through flight crew rostering; increasing efficiency by promoting direct routing; and increasing efficiency through greater flight deck automation. It is argued that the increases in operational efficiency (which is taken to be almost synonymous with cost) taking solely a human factors perspective will be minimal. To truly enhance operating efficiency the human component in any system cannot be examined in isolation from all other components.